Relationship of Caries between Primary Molars and the Permanent First Molar - A Comparative Study - Youmna Almasri; Diala Arhil; Abdulmalek Harfoush; Imad Barngkgei (Indian Journal of Dental Research)
Context: Dental caries is a multifactorial disease that affects large segment of population worldwide. Aim: To evaluate the detailed relationship between carious status of primary molars and permanent first molars among 8.5–10 years old children. Methods and Materials: Two-hundred and seven children were included in this cross-sectional study. The permanent incisors were fully erupted, the primary canines had no caries experience, and premolars were not erupted. The dentition status of the primary molars and permanent first molars was examined according to the World Health Organization criteria. Statistical Analysis Used: Pearson correlation, independent sample t-test, and linear and logistic regression analysis were used. The significance level was set at 0.05. Results: The mean (standard deviation) of decay, missing and filled teeth/surface for primary molars and permanent first molar (dmfs&dmft/DMFS&DMFT) were 4.12 (2.53), 8.40 (7.43), 0.77 (1.16) and 1.01 (1.81), respectively. Weak and medium correlations were found between d-component and D-component (r < 0.5), though statistically significant (P value < 0.001). Moreover, there was a relationship between the number of primary molars caries and the presence of caries on the permanent first molar located in the same side and jaw of these primary molars and those located in the opposite side and jaw of the primary molars. Conclusion: Nearly one-fifth of the caries on the permanent molars might be attributed to caries on the primary molars among 8.5–10 years-old children. The odds ratio of developing caries on the permanent first molars was 1.5 for children with primary molars caries in comparison to children with no primary caries.